Epidemiology of idiopathic cardiomyopathy in Japan: results from a nationwide survey. Issue 2 (1st February 2002) - Miura, K; Nakagawa, H; Morikawa, Y; Sasayama, S; Matsumori, A; Hasegawa, K; Ohno, Y; Tamakoshi, A; Kawamura, T; Inaba, Y
Abstract : Objective: To estimate the total number of patients with idiopathic cardiomyopathy in Japan and the prevalence of the disorder. Design: A nationwide epidemiological survey. Setting: Hospitals selected randomly from among all hospitals in Japan. Patients: Patients presenting with any of the three types of idiopathic cardiomyopathy: dilated cardiomyopathy, hypertrophic cardiomyopathy, and restrictive cardiomyopathy. Main outcome measures: The total number of patients in Japan was estimated using the sampling and response rates in each stratum with respect to hospital size. The second survey was conducted for patients reported in the first survey in order to obtain detailed information, including age, sex, and specific clinical data. Results: Estimated patient totals and 95% confidence intervals (CI) were 17 700 (95% CI 16 500 to 18 800) for dilated cardiomyopathy, 21 900 (95% CI 20 600 to 23 200) for hypertrophic cardiomyopathy, and 300 (95% CI 250 to 350) for restrictive cardiomyopathy. Crude prevalence per 100 000 population was estimated as 14.0 for dilated cardiomyopathy, 17.3 for hypertrophic cardiomyopathy, and 0.2 for restrictive cardiomyopathy; crude incidence per 100 000 person-years was estimated as 3.58, 4.14, and 0.06, respectively. Conclusions: The total number and prevalence of patients with idiopathic cardiomyopathy in Japan are estimated for the first time in a nationwide survey. The prevalence of dilated cardiomyopathy in Japan appears to be about half that of Western populations, while that of hypertrophic cardiomyopathy is about the same.